Design and Demonstration of a DAB Based RadCom System - Norrie, Grant (Department of Electrical Engineering, 2024)
The electromagnetic spectrum is becoming increasingly congested due to the growing demand for telecommunications and remote sensing applications. This poses the risk of spectrum bands being reallocated from radar to these applications with organisations such as telecommunication companies willing to pay billions of dollars to use particular bands. Traditionally, this limitation is overcome by the use of passive radar that leverages off of existing communication based transmitters for radar based applications. This passive radar approach to sharing the spectrum is a commensal approach with communications first and radar second. But these increasingly narrow bands allocated for radar and the complications of commensal systems provide the motivation to merge the traditionally separate communication and radar systems into a single radar first radar-communications or ‘RadCom' system. The goal of this system is to use a single hardware platform to transmit a standards based waveform, that can be used for both radar and communication applications simultaneously in a symbiotic nature. The development of the RadCom system was therefore divided into four sub-systems. This includes the development of the signal generation, communications, and radar processing chains while the final sub-system developed was the software-defined-hardware testbed. Development began with the adjustment of the Digital Audio Broadcasting signal. These DAB signals are described by the DAB mode structure, defining their time and frequency domain characteristics. This structure was generalised to describe the RadCom signal and used by the signal generation chain to facilitate the generation of Orthogonal Frequency Division Multiplexed signals. The same generation chain provided the ability to simultaneously encode bitstreams onto OFDM signals. The communication processing chain was developed to demodulate and decode the RadCom signal, thereby extracting the encoded bitstream. The radar processing chain was designed to implement clutter map removal, pulse cancellation and channel alignment procedures to complete range Doppler map processing. Finally, the testbed was developed using two Ettus USRP N210 SDR devices with SBX daughterboards as well as two 2.4 GHz antennas. This ensured that the system was able to simultaneously transmit and receive signals. Each subsystem was individually verified for correct operation prior to the completion of field tests. These verification procedures included bit error rate calculations, FERS simulations and controlled loopback tests. Field tests were conducted once these validation tests were completed. This involved the completion of a communications test, a static range test and moving target tests. Tests contained validation mechanisms such as reference bitstreams, GPS measurements and equivalent FERS simulations. These provided measurements to judge system performance against. Results included a bit error rate of 0 % for a close range direct link communications test, an expected 100 m static range measurement and GPS verified range doppler measurements. These results therefore demonstrated the correct operation of the system and therefore completed the design and demonstration of the RadCom system.